Feminism Found In Tjoet Tja Dhien 1988 Film - Meilana, Ayu; Effendi, Dedi; Oktariza, Dodi (Universitas Muara Bungo, 2025)
This research analalyzes about Feminism found in Tjoet Tja Dhien 1988 film. This research uses the object of the film Tjoet tja dhien 1988 by erros djarot. The purpose of this research are to find the type of feminism and describe the researcher’s perspective by the female gaze theory in the film Tjoe Tja Dhien 1988. This research uses qualitative descriptive method by Moleong (2017) , qualitative research is a research that intends to understand the phenomena about what is experienced by research subjects such as behavior, and perceptions.The data are presented in dialogue or Subtitle and scene related to feminism and the researcher perspective in the film Tjoet tja dhien 1988. Data analysis through four procedures: identification, classification, analysis and conclusions from all data. In this research, the researcher used theory of Feminism by Jane Freedman (2001) And theory of Researcher perspective by Laura Mulvey (1975).The results of this research were found 15 data of feminism and followed by 15 data of researcher’s perspective of the research. All of data analyzed in Tjoet Tja Dhien 1988 Film. The 15 data of Feminism that found divided into 2 types of feminism they are: 12 data Liberal feminis, and 3 data Marxism feminism. Beside, the 15 data of the researcher perspective ,the researcher also found perspective , it is Female gaze above 14 data and One of them not include into researcher perspective. If the 15 data found would be too much if all were entered, the researcher only took 10 data to represent the 15 data found with 2 different types, 7 liberal data and 3 Marxist data.